Determinantes da sustentabilidade empresarial: uma análise das empresas listadas no Dow Jones sutainability world index e no índice de sustentabilidade empresarial da BM&FBOVESPA - Pena, Thiago José Silva (2017)
Sustainable development is an aspiration that society has been seeking to ensure quality and perpetuity of its resources. Through their management, companies search ways to adapt to this stance. A sustainable business approach is more profitable as it encourages increase in revenues through the designing of better products. It also allows the creation of new business models. The present researchaims to analyze the determinants of corporate sustainability using as a proxy for corporate sustainability the listing in the Dow Jones Sustainability World Index (DJSI) and in the Corporate Sustainability Index of the BM&FBOVESPA (ISE). We had two different samples in this study. The first one was composed by firms eligible to DJSI and the second one was composed by firms eligible to ISE. We used two different samples given the different criteria for listing in each index. Our logistic regression models used participation in the sustainability indices as dependent binary variable. We tested the hypotheses that corporate sustainability is affected by firm’s size, leverage, financial capacity, profitability and growth opportunities. In DJSI samples we found out that firm size was positively related to the sustainable performance. We also found out that ROE is positively related to sustainable performance, indicating that more profitable firms are more sustainable. For ISE sample the results show that size and profitability were determinants of sustainable performance, exhibiting a positive relation, confirming the results obtained in the DJSI sample. Growth opportunities were positively related to sustainable performance only when they were represented by revenue growth.